2019
DOI: 10.1111/tme.12629
|View full text |Cite
|
Sign up to set email alerts
|

Current approaches to increase blood donations in resource‐limited countries

Abstract: SUMMARY Background Low‐ and middle‐income countries (LMIC) suffer from chronic or seasonal blood shortage. The first review was published in 2007. Methods The review of literature since 2005 presented here uncovered a fairly large number of articles justifying the grouping of blood donation issues into five geographical areas sharing common background. These are Sub‐Saharan Africa (SSA), Muslim countries, India, China/South East Asia and Latin America/Caribbean islands (LA&C). Results SSA countries start colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 88 publications
0
18
0
3
Order By: Relevance
“…We opine that the reason for this low proportion of respondent who had donated before may be this University is fully residential and students spend at least 8-9 months of the year on campus where there are currently no blood bank services in the affiliated teaching hospital. We believe that intention to donate could be translated into a donation if the opportunity is provided for the students as a recent review observed that knowledge about blood donation is associated with commitment to blood donation [19]. A few studies in Ethiopia demonstrated that health professionals who knew about blood donation either as a requirement for their training before qualifying or as a result of their familiarity with the practice while on the job were more likely to donate blood than those who do not know much about blood donation [17,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We opine that the reason for this low proportion of respondent who had donated before may be this University is fully residential and students spend at least 8-9 months of the year on campus where there are currently no blood bank services in the affiliated teaching hospital. We believe that intention to donate could be translated into a donation if the opportunity is provided for the students as a recent review observed that knowledge about blood donation is associated with commitment to blood donation [19]. A few studies in Ethiopia demonstrated that health professionals who knew about blood donation either as a requirement for their training before qualifying or as a result of their familiarity with the practice while on the job were more likely to donate blood than those who do not know much about blood donation [17,24].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, any strategy to improve blood supply in Africa must aim at increasing the pool and retaining the VNRD group [17,18] as it is well known that VNRD provides the safest source of blood for transfusion [7]. The consensus on the age to start recruiting donors is 16-18 years, and it is expected that this age group can be educated, and if they eventually became VNRD, they would do so for a long time, thereby improving the supply of safe blood statistics in Africa [19].…”
Section: Introductionmentioning
confidence: 99%
“…A nationwide ban on the FRD went into effect on April 1, 2018 in China. With the “more donors, more blood “ belief, it was believed that banning the FRD would cause serious consequences related to the shortage of blood supply [ 8 , 12 ]. However, a phenomenon of “fewer donors, more blood” for the plateletpheresis donation has been emerging in Guangzhou Blood Center and Chengdu Blood Center since the implement of the FRD ban in China, even though there is no substantial difference in the publicity and recruitment of blood donation between before and after the FRD ban in the two blood centers.…”
Section: Introductionmentioning
confidence: 99%
“…There is an ongoing debate over the family/replacement donation (FRD) policy in uencing both shortage and safety of blood supply [3][4][5]. FRD, also called mutual donation, occurs when family members are required to donate blood to replace each unit used by their friend or relative [6] Currently, the FRD is legitimate and considered to be indispensable to the transfusion services in many countries with the limited resources [7][8][9]. Although this type of blood donation may provide short-term solutions for dealing with the shortage of blood supply [10], it increases public distrust in voluntary blood donation and affects the quality and safety of donated blood [11].…”
Section: Introductionmentioning
confidence: 99%
“…A nationwide ban on the FRD went into effect on April 1, 2018 in China. With the "more donors, more blood " belief, it was believed that banning the FRD would cause serious consequences related to the shortage of blood supply [8,12]. However, a phenomenon of "fewer donors, more blood" for the plateletpheresis donation has been emerging in the eld since the implement of the FRD ban in China.…”
Section: Introductionmentioning
confidence: 99%